Otolaryngological Aspects of Sjögren's Syndrome. Issue 5785 (20th November 1971) - Doig, J. A.; Whaley, K.; Dick, W. C.; Nuki, G.; Williamson, J.; Buchanan, W. W.
Abstract : Twenty-two patients with Sjögren's syndrome uncomplicated by a connective tissue disorder, 31 with Sjögren's syndrome complicated by rheumatoid arthritis, and 21 with rheumatoid arthritis alone were studied with particular reference to changes in the ears and in the upper respiratory and digestive tracts. Epistaxis, soreness and dryness of the throat, dysphagia, and hoarseness were common symptoms, and rhinitis sicca and postcricoid narrowing were not uncommon features of the Sjögren groups. Oesophagoscopy in one patient revealed a web identical to that found in Paterson/Brown Kelly syndrome; none of the patients, however, had an iron-deficiency anaemia or koilonychia. There was an increased frequency of deafness in all groups, and the deafness tended to be conductive in the Sjögren groups and sensorineural in the rheumatoid arthritis group.